The articles in this edition cover a wide variety of interrelated themes - Green, S (Social Work/Maatskaplike Werk, 2002)
This issue contains two articles that examine the strengths perspective as an alternative to other intervention models in social work. One by Gray and Colin Collett van Rooyen provides an overview of the strengths perspective in social work which has contributed to an important paradigm shift away from the dominant deficits-based mental health paradigm, anti-oppressive practice models and rigid mindsets that dominated social work interventions for many years. After a critical review of the domains in which strength-based approaches have taken hold, the authors focus on lessons from practice to show convincingly that the strengths perspective provides social workers with a perspective that focuses on the positive elements when assessing people and situations, while not denying that negative elements exist. The other, by Mashego and Lombard, explains comprehensively how Project-Go is embedded in the theoretical perspectives of the ecological systems perspective, the contextual perspective, the developmental perspective and the strengths perspective. The authors report on a study conducted in the Gauteng province among probation officers and social workers who are working with children and youths in residential care facilities. The implementation of Project-Go was evaluated on the basis of what social workers had to say about their experience, understanding and perception regarding the whole process since it was initiated. The authors found that the majority of the respondents were in agreement with the principles, philosophy, values and beliefs of the concept and process of Project-Go. They conclude that Project-Go, as a model, recognises that children, youths and families have the strengths and capabilities to change. Cronje presents an interesting research project undertaken to determine the factors influencing the life satisfaction of a group of elderly retired Black South African women who had worked as domestic workers. After a literature review the author offers the story of thirty women, told through different voices, and she discusses the group’s overriding feeling of meaningfulness and life satisfaction.